Spontaneous Hematomyelia Associated with the Use of Non–vitamin K Antagonist - Park, Moon Soo; Moon, Seong-Hwan; Jang, Seung Bo; Kim, Jeoung Woo; Sung, Paul S. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Vitamin K antagonists have been frequently prescribed as anticoagulants with the potential side effect of spontaneous hematomyelia with a poor prognosis. However, to our knowledge, there has been no report of spontaneous hematomyelia combined with the use of a non–vitamin K antagonist. A 63-year-old man presented with left leg weakness, impaired sensation, and urinary retention while taking rivaroxaban (non–vitamin K antagonist) for 4 months for atrial fibrillation. Anticoagulant agents were discontinued. Methylprednisolone pulse therapy was administered without surgical hematoma evacuation. Three months after the initial development of the hematomyelia, the symptoms improved to grade 5 for both lower extremities, and there was complete recovery in sensory and urinary functions. This might be the first description of a complete recovery of neurologic deficits without hematoma evacuation in spontaneous hematomyelia patients caused by non–vitamin K antagonist therapy.
Keywords: anticoagulant; rivaroxaban; spinal intramedullary hematoma